1981
DOI: 10.1364/ao.20.002539
|View full text |Cite
|
Sign up to set email alerts
|

Phase fluctuation optical heterodyne spectroscopy of gases

Abstract: The theory underlying the use of the phase fluctuation optical heterodyne (PFLOH) technique in studies of molecular relaxation, thermal conduction, and extremely weak absorptions in the gas phase is presented. Several new solutions to the heat conduction equation, with and without mass diffusion, which are appropriate to pulsed, cw, and modulated-cw laser modulation of weakly absorbing gases, are presented. Experiments employing pulsed and modulated-cw excitation have borne out the essential predictions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 11 publications
2
68
0
1
Order By: Relevance
“…As a detailed discussion of the photothermal technique can be found elsewhere (Sedlacek 2006;Owens et al 1999, Lin andCampillo 1985;Bialkowski 1996;Davis 1980;Davis and Petuchowski 1981;Dovichi 1990;Davis 1996), only the highlights that are relevant to the present discussion will be presented. At its most fundamental level, the PTI technique measures the optical pathlength change that one arm of an interferometer experiences (referred to as the "probe" arm) relative to the other arm of the interferometer (called the "reference").…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…As a detailed discussion of the photothermal technique can be found elsewhere (Sedlacek 2006;Owens et al 1999, Lin andCampillo 1985;Bialkowski 1996;Davis 1980;Davis and Petuchowski 1981;Dovichi 1990;Davis 1996), only the highlights that are relevant to the present discussion will be presented. At its most fundamental level, the PTI technique measures the optical pathlength change that one arm of an interferometer experiences (referred to as the "probe" arm) relative to the other arm of the interferometer (called the "reference").…”
Section: Theorymentioning
confidence: 99%
“…For the interferometer of the type just described, it can be shown that the measured detector current (Davis 1980;Davis and Petuchowski 1981;Lin and Campillo 1985;Fluckiger et al 1985 ;Bialkowski 1996;Davis 1996;Owens et al 1999;Sedlacek 2006), under quadrature conditions (i.e., φ ref − φ probe = (2n + 1) π 2 where φ is the phase of each respective arm), reduces to…”
Section: Theorymentioning
confidence: 99%
“…Back in the mid 1980's, Lin and co-workers [3,16] described the in situ measurement of the aerosol absorption of ammonium sulfate using, what the authors referred to as, phase fluctuation optical heterodyne spectroscopy (PFLOH). § [2,24] These initial experiments used a Mach-Zehnder (MZ) configuration, where a single-frequency probe laser (He-Ne) was split by a 50/50 beam splitter (BS) with one arm of the interferometer directed into a sample cell containing aerosol-laden air and where a counter-propagating "pump" laser (linetunable CO 2 ) overlapped this "probe" beam. Absorption of the pump laser light by the aerosol resulted in local heating, which, in turn, caused an expansion of the air in the cell.…”
Section: Methodsmentioning
confidence: 99%
“…If we let the optical fields of the signal (probe beam) and local oscillator (reference beam) be represented by (2) where A j , ω and φ represent the amplitude, angular frequency and phase; and, where ∆φ t ( ) is the induced time-dependent phase fluctuations, it can be shown, for a square law detector, that the current in the detector, I t…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation